1993
DOI: 10.1177/088307389300800409
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit- Hyperactivity Disorder and Asymmetry of the Caudate Nucleus

Abstract: The neurologic basis of attention deficit-hyperactivity disorder (ADHD) is poorly understood. Based on previous studies that have implicated metabolic deficiencies in the caudate-striatal region in ADHD, we employed magnetic resonance imaging to investigate patterns of morphology of the head of the caudate nucleus in normal and ADHD children. In normal children, 72.7% evidenced a left-larger-than-right (L > R) pattern of asymmetry, whereas 63.6% of the ADHD children had the reverse (L < R) pattern of asymmetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
156
1
8

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(171 citation statements)
references
References 31 publications
6
156
1
8
Order By: Relevance
“…Other brain nuclei including the basal ganglia were also found to be altered. For example, two studies described a reduced volume of the left caudate nucleus in children with ADHD (Filipek et al 1997;Hynd et al 1993). Two further studies found a reduced volume of the globus pallidus in children with ADHD compared to normal controls (Aylward et al 1996;Castellanos et al 1996b).…”
Section: Functional and Structural Abnormalitiesmentioning
confidence: 99%
“…Other brain nuclei including the basal ganglia were also found to be altered. For example, two studies described a reduced volume of the left caudate nucleus in children with ADHD (Filipek et al 1997;Hynd et al 1993). Two further studies found a reduced volume of the globus pallidus in children with ADHD compared to normal controls (Aylward et al 1996;Castellanos et al 1996b).…”
Section: Functional and Structural Abnormalitiesmentioning
confidence: 99%
“…Caudate studies have suggested smaller caudate in ADHD but have been inconsistent. Some have reported decreased volume of caudate in ADHD patients relative to controls (SemrudClikeman et al, 2006); Castellanos et al, 2002;Hynd et al, 1993), whereas others found no volume differences or larger caudate in ADHD patients (Mataro et al, 1997). Castellanos et al (2002) indicated that initially smaller caudate volumes showed normalization in ADHD males during late adolescence, possibly reflecting the clinical observation that the hyperactivity of ADHD tends to diminish during this time.…”
Section: Selected Adhd Imaging Datamentioning
confidence: 99%
“…Multiple anatomic MRI (aMRI) studies of ADHD have revealed abnormalities in frontal areas [Castellanos et al, 1996[Castellanos et al, , 2000[Castellanos et al, , 2002Filipek et al, 1997;Hesslinger et al, 2002;Kates et al, 2002;Mostofsky et al, 2002] and interconnected subcortical structures including the caudate [Hynd et al, 1993;Castellanos et al, 1996;Filipek et al, 1997;Mataro et al, 1997], putamen [Wellington et al, 2006], globus pallidus [Basser and Pierpaoli, 1996], and cerebellum [Castellanos et al, 1996;Berquin et al, 1998;Mostofsky et al, 1998]. At the cerebral cortical level, observation of decreased volume of several frontal [Castellanos et al, 1996;Filipek et al, 1997;Hesslinger et al, 2002;Mostofsky et al, 2002] and nonfrontal regions suggests that abnormalities are not localized to a specific area.…”
Section: Anomalous Brain Development In Adhdmentioning
confidence: 99%